Sickness and the Power of Healing Prayer in 2 Kings 20:1–11 and Isaiah 38:1–22 - Udoekpo, Michael Ufok (Religions, 2024)
2 Kings 20:1–11; Isaiah 38:1–22 and 2 Chronicles 32:24–26 discuss Hezekiah’s sickness and the power of healing prayer. They are called Hezekiah-Isaiah narratives since they deal not only with (a) the threats and salvation of Jerusalem from Assyria, (b) the disease and the miraculous recovery or healing (ḥāyâ/rāքā’) of Hezekiah and description of the representatives from Babylon, but share a common narrative pattern in which Hezekiah is healed with a poultice/lump of fig tree (dəbelet təʾnim), having received advise and healing support from God’s messenger, Isaiah. Past scholars have approached this text differently, searching for its dating, literary growths, differences, originality with the desire to reveal the history of the various traditional components and relationship among parallel texts, as well the prophetic and kingly images of Isaiah and Hezekiah. Built on this past scholarship and African cultural perspectives and experiences, this work contextually, historically and theologically study, develop and analyze the story of Hezekiah’s sickness and healing.